The Child Anxiety Impact Scale (CAIS): Examining Parent- and Child-reported Impairment in Child Anxiety Disorders - Langley, Audra K. (2013)
OBJECTIVE: The purpose of the current investigation was to examine the factor structure, reliability, and construct validity of both the Child and Parent version of the Child Anxiety Impact Scale (CAIS) using data obtained from the Child/Adolescent Anxiety Multimodal Study (CAMS; Walkup et al., 2008). METHOD: The CAIS child and parent versions measure anxiety-related functional impairment in school, social and family domains. Participants were 488 children ages 7 to 17 (mean age 10.7; SD=2.8 years) enrolled as part of the CAMS study across 6 sites and their primary parent or caregiver. Families participated in a structured diagnostic interview and then completed the CAIS along with other measures. RESULTS: Confirmatory factor analysis revealed that the a priori three factor structure (school, social, and home/family) for the CAIS parent- and child-report was a reasonable fit, with a Comparative Fit Index (CFI) of .88 and Root Mean Square Error of Approximation (RMSEA) of .05. Internal consistency was very good for total score and subscales of both versions of the scale (Cronbach’s alpha ranged from = .70–.90). The CAIS total scores demonstrated good construct validity, showing predicted significant correlations with the CBCL Internalizing Scale, the MASC and SCARED Total Scores, the PARS and the CGAS. In addition, CAIS Social and School subscales were significantly related to similar subscales on the CBCL, SCARED, and MASC. CONCLUSIONS: The results provide support that the CAIS is a reliable and valid measure for the assessment of the impact of anxiety on child and adolescent functioning.